The Ideal Model of Law Education to Achieve Progressive Law Enforcement - Sudiyana, Sudiyana (The Indonesian Journal of International Clinical Legal Education, 2019)
The legal education in Indonesia tends to produce graduates who believe in legal positivism. The principle of legal positivism runs as follows. Firstly, it encourages law enforcers to think and act in any legal formalistic way. Secondly, it places judges as the mouthpiece of the law; who cannot express to make decisions that satisfy a sense of social justice and substantive justice. How the ideal model of legal education is formed in order to create more progressive law enforcement. This article is based on the socio-juridical approach by underlying the analysis of the law and regulations which are related to the application of legal education in the community. The legal education is oriented to legal positivism that results in law enforcement with the understanding of law based on the abstract values, not on the values that live and thrive in society, so that the understanding of the law in a legal sense is more repressive, and not responsive. Law is understood as unfunctional and un-pragmatic things therefore understanding of law is the law that merely protects the elite group of citizens, in such a way that equality before the law and the rule of law don’t work. Legal education in the future should be based on the sociological aspects of prioritizing the principles of social justice and the benefits for the community, instead of legal certainty only. Legal education will produce a responsive law enforcement that put substantive fairness and social justice as a legal purpose.